Pendekatan Budaya dan Penginjilan dalam Mengubah Keterbelakangan Suku Dayak Kanayatn Kabupaten Landak Kalimantan Barat - Nicodemus Sabudin (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Preaching the Gospel is an obligation for every believer, a duty and calling as followers of Christ. This can be achieved through various methods to reach every tribe or region, in the context of preaching the Gospel. This preaching of the Gospel can be done using the methods God has given to humans to proclaim His name to all people, including the Dayak Kanayatn tribe, located in Landak Regency, West Kalimantan. A contextual approach is needed as a strategy in preaching the Gospel. The purpose of this study is to determine the cultural and evangelistic approaches to changing poverty, ignorance, and backwardness among the Dayak Kanayatn tribe. By employing a descriptive historical approach, namely utilizing data, archives, and past documents, it is possible to understand a current situation and derive insights that can inform future decisions. Data collection techniques include literature studies, interviews, and observations. The results of this study are an approach through culture, evangelism, and discipleship that can be used as a strategy to change the backwardness of the Dayak Kanayatn tribe.